Effects of cybertechnology on body and identity in selected american cyberpunk and post-cyberpunk fictions - Soofastaei, Elaheh (2019)
Science fiction is a famous genre of literature by which writers try to visualise scenes of the near or far future where many technological aspects are seen in human life. Media and computer technology have played an undeniable role in illustrating different science fictional images in stories. From the late twentieth century onwards, human life and culture have been on the periphery of the cybertechnological revolution. Since then, many writers have illustrated the dream of humans living in a place without biological boundaries, time and/or place limitations: with the advent of cybertechnology, this dream is about to come true. Post/cyberpunk fiction as one of the sub-genres of science fiction, would illustrate the aspects of fictional human life through this progressing technology. In post/cyberpunk, characters' bodies usually interact with the computer and network. In this study, my textual analysis will focus on four American novels from the late twentieth to twenty-first centuries, namely This Perfect Day (1970) by Ira Levin, Neuromancer (1984) by William Gibson, Feed (2002) by M.T. Anderson, and Ready Player One (2011) by Ernest Cline. These texts will be studied from the perspectives offered by critics, such as Tim Jordan, Katherine Hayles, Jean Baudrillard, Dani Cavallaro, Donna Haraway, Woodrow Barfield and Megan L. Musgrave through the concepts of cyberspace and cyborg under the umbrella term of cyberculture. This study aims to examine various factors of body formation, including jack-in, simulation, uniformity and consumerism in the selected novels; it also aims to investigate the consequences of matrix body and materialized avatar body through the concept of cyberspace, and hacked body and consumer body through the concept of cyborg. All the objectives will be examined within the concepts of cyberspace and cyborg in the selected post/cyberpunk novels. More specifically, the protagonists - Case and Molly in Neuromancer become matrix forms through jack-in with an immersive identity, and Wade and Art3mis in Ready Player One turn into materialized avatar bodies through simulation with an on/off identity. In addition, Chip and Lilac in This Perfect Day become hacked bodies through uniformity with a double identity, and Violet and Titus in Feed turn into consumer cyborgs through consumerism with a mindless identity. This study contributes to the general decaying of humanity in the characters of the stories through new forms of body and different identities which are made by cybertechnology. The analysis of the selected novels in this study have some findings which help future literary studies to have a better understanding about the effects of cybertechnology on human body, life, and society. Such literary researches can be helpful for humans’ real life in not-too-distant future. In the end, I look at the consequences of effects of cybertechnology on body and identity.